Novel CT domain-encoding splice forms of CTGF/CCN2 are expressed in B-lineage acute lymphoblastic leukaemia. Issue 8 (August 2015) - Welch, M.D.; Howlett, M.; Halse, H.M.; Greene, W.K.; Kees, U.R.
Highlights: CTGF is aberrantly expressed in a range of neoplasms including B-lineage ALLs. We identified by sequencing CTGF mRNA isoforms in primary pre-B ALL specimens. Most primary specimens express a novel CTGF mRNA in additional to canonical CTGF . Abstract: Introduction: Connective tissue growth factor ( CTGF / CCN2 ) has been shown previously to be aberrantly expressed in a high proportion of paediatric precursor B cell acute lymphoblastic leukaemia (pre-B ALL), suggesting a potential oncogenic role in this tumour type. We therefore assessed CTGF mRNA transcript diversity in B-lineage ALL using primary patient specimens and cell lines. Methods: CTGF mRNA expression was evaluated by quantitative real-time PCR and Northern blotting. We performed a structural analysis of CTGF mRNA by nested reverse-transcriptase PCR and examined CTGF protein diversity by immunoblotting. Results: Northern blot analysis of pre-B ALL cell lines revealed short CTGF transcripts that were expressed in association with the active phase of cellular growth. Structural analysis confirmed the synthesis of several novel CTGF mRNA isoforms in B-lineage ALL cell lines that were uniformly characterised by the retention of the coding sequence for the C-terminal (CT) domain. One of these novel spliceforms was expressed in a majority (70%) of primary pre-B ALL patient specimens positive for canonical CTGF mRNA. Evidence that these alternative transcripts have coding potential was provided by cryptic CTGF proteins of predicted size detected by immunoblotting. Conclusion: This study identifies for the first time alternative splicing of the CTGF gene and shows that a short CTGF splice variant associated with cell proliferation is expressed in most cases of primary CTGF-positive pre-B ALL. This novel variant encoding only the CT domain may play a role in pre-B ALL tumorigenesis and/or progression.